Strategi Pembelajaran Matematika Madrasah Ibtidaiyah Berintegrasi Nilai-nilai Islam - Mimi Hariyani (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Nowadays, learning mathematics is still separated with Islamic religious education. Yet at the latest in madrasah curriculum requires the integration of Islamic values in each subject. Integration of Islamic values in the learning of mathematics itself is often considered difficult because teachers have not been accustomed to apply it. Actually, integrating Islamic values into learning math is not difficult, it can be done in various ways such as: alwaysmention the name of Allah, the use of the term, visual illustrations, or examples of applications, insert the relevant verse or hadith, search history, network topics, symbols kauniah verses.